(3r-4s)(-5s)=

Simple and best practice solution for (3r-4s)(-5s)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3r-4s)(-5s)= equation:


Simplifying
(3r + -4s)(-5s) = 0

Remove parenthesis around (-5s)
(3r + -4s) * -5s = 0

Reorder the terms for easier multiplication:
-5s(3r + -4s) = 0
(3r * -5s + -4s * -5s) = 0
(-15rs + 20s2) = 0

Solving
-15rs + 20s2 = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-20s2' to each side of the equation.
-15rs + 20s2 + -20s2 = 0 + -20s2

Combine like terms: 20s2 + -20s2 = 0
-15rs + 0 = 0 + -20s2
-15rs = 0 + -20s2
Remove the zero:
-15rs = -20s2

Divide each side by '-15s'.
r = 1.333333333s

Simplifying
r = 1.333333333s

See similar equations:

| 6f-5f=7 | | 5y=8x-58 | | 6x=x+7 | | 3/7x=83/5 | | 3(2x-5)=12(2x-3)-15 | | y+1200=400x | | 19-5x=5-7x | | X+2X+3X+2X+X=360 | | 23=x+2x(x+3) | | 2(x-2)-x-4=3x | | -2x+28=4 | | 6x-3y=33 | | 2k-2=3(k-2) | | 3x+4y-5x+8y=ax+by | | 7a-2a=9 | | 30y+6=30 | | 3x-90=90 | | 4x^2-24x+52=0 | | 3x-9x+15y+6y=0 | | -16+4m=-m+5m-m | | 3-69=9-5a | | 30-7r=r+6 | | x(2x+3)=216 | | 10g+17=7g+11 | | -3(3-d)=18 | | -3(3-d)+4=4 | | 4(t-7)+4=-4 | | 6y-11=19 | | 12f-4=2f+9 | | 4x=22-6 | | 5n+8n+4= | | x=96-0.5*(96-0.5*x) |

Equations solver categories